Mampukah Moralitas Memoderasi Determinan Kepatuhan Wajib Pajak Kendaraan Bermotor? - Rahma, Faradiba Alivia; Maulana, Muhammad Harris; Ahoinai, Matheus Fanu; Hatta, Atika Jauharia (E-Jurnal Akuntansi; Vol 32 No 12 (2022)DO - 10.24843/EJA.2022.v32.i12.p05, 2022)
The study aims to determine the effect of morality in moderating tax awareness, tax literacy, and money ethics on motor vehicle tax compliance at the SAMSAT Special Region of Yogyakarta. The variables used in this study are tax awareness, tax literacy, money ethics, and morality which in this case are the moderating variables. The selection of the research sample used a purposive sampling method and 75 respondents were obtained. The analysis tool used multiple linear regression and Moderated Regression Analysis (MRA). The results of data analysis show that tax awareness and tax literacy have a positive effect on tax compliance. Meanwhile, money ethics has no influence on tax compliance. In addition, it was found that morality is able to moderate taxpayer awareness in a negative direction. However, morality is not able to moderate tax literacy and money ethics towards compliance in paying motor vehicle taxes. Keywords: Tax Compliance; Tax Awareness; Tax Literacy; Money Ethic; Morality.